Upper Holocene sea level changes in the West Saronic Gulf, Greece. (16th May 2016) - Kolaiti, E.; Mourtzas, N.D.
Abstract: Along the Peloponnesian coast of the Saronic Gulf and on the coast of Aegina and Poros islands, submerged coastal geomorphological features related directly with submerged ancient coastal constructions, indicate three distinct sea levels. Submerged tidal notches incised on the carbonate basement, beachrocks formed in the intertidal zone and archaeological indicators, such as the ancient harbour installations in Kenchreai and Epidaurus and on Aegina island, the extended coastal buildings and constructions in Agios Vlasis, Psifta and Palaiokastro-Methana, and Vagionia on Poros island, are used to determine the age and magnitude of submersion and the extent of the Upper Holocene marine transgression. By the correlation of geomorphological, historical and archaeological indications three distinct sea levels were identified, at −3.30 ± 0.15 m,  −0.90 ± 0.15 m and −0.55 ± 0.05 m. Initial change in sea level occurred definitely after AD 400 ± 100. The intermediate change is dated between AD 1586 and 1839, and the most recent change after 1839. Sea transgression followed a long period of sea level stability, which lasted at least 2200 years, from the Middle Bronze Age to the Late Roman period.